Never say die - Horowitz, Anthony, 1955- (Horowitz, Anthony, 1955- Alex Rider adventure., 2018)
Alex is struggling to come to terms with the death of his caregiver and best friend, Jack Starbright. But a three-word email changes everything, and now Alex is heading to Egypt with hope that Jack might still be alive. But as he searches for his friend, he uncovers a new terrorist plot that will have him traveling from Egypt to the the South of France in the hopes of stopping the terrorists in their tracks.